Pseudobarbus kubhekai sp. nov., a new redfin (Teleostei, Cyprinidae) from KwaZulu-Natal, South Africa - Fatah Zarei; Xiluva Mathebula; Albert Chakona (Zoosystematics and Evolution)
A recent phylogeographic analysis of the remnant populations of Pseudobarbus quathlambae from Lesotho and South Africa revealed the existence of three allopatrically distributed lineages: (i) one in eastern Lesotho, (ii) one in Mohale, central Lesotho, and (iii) a third lineage in the Umzimkhulu (= Mzimkhulu) River, KwaZulu-Natal, adjacent to the Mkhomazana River (type locality), where the species has gone extinct. The present study provides morphological and osteological evidence corroborating the distinctiveness of the Umzimkhulu River population from all other populations (extant and extinct) of P. quathlambae, supporting their recognition as distinct species. Herein, we describe the Umzimkhulu River population as a new species, Pseudobarbus kubhekai. The new species, a single barbeled redfin, differs from all currently recognized congeners by having 51–56 scales in lateral-line series (vs. 60–72 in P. quathlambae and 25–45 in the other species). Proposed steps to resolve the taxonomic status of P. quathlambae from other localities (Mkhomazana population, Eastern Lesotho Highlands, and Mohale lineages) are presented.